Cyclodextrin modulation of gallic acid in vitro antibacterial activity - Pinho, Eva (2015)
The substitution of large spectrum antibiotics for natural bioactive molecules (especially polyphenolics) for the treatment of wound infections has come into prominence in the pharmaceutical industry. However, the use of such molecules depends on their stability during environmental stress and on their ability to reach the action site without losing biological properties. The application of cyclodextrins as a vehicle for polyphenolics protection has been documented and appears to enhance the properties of bioactive molecules. Therefore, the encapsulation of gallic acid, an antibacterial agent with low stability, by -cyclodextrin, (2-hydroxy) propyl--cyclodextrin and methyl--cyclodextrin, was investigated. Encapsulation by -cyclodextrin was confirmed for pH 3 and 5, with similar stability parameters. The (2-hydroxy) propyl--cyclodextrin and methyl--cyclodextrin interactions with gallic acid were only confirmed at pH 3. Among the three cyclodextrins, better gallic acid encapsulation were observed for (2-hydroxy) propyl--cyclodextrin, followed by -cyclodextrin and methyl--cyclodextrin. The effect of cyclodextrin encapsulation on the gallic acid antibacterial activity was also analysed. The antibacterial activity of the inclusion complexes was investigated here for the first time. According to the results, encapsulation of gallic acid by (2-hydroxy) propyl--cyclodextrin seems to be a viable option for the treatment of skin and soft tissue infections, since this inclusion complex has good stability and antibacterial activity.